Improving air traffic control by combining centralized and decentralized solutions - Raziq, Omayma; Khaili, Mohamed El; Nhaila, Hasna; Khiat, Azeddine (Edelweiss Applied Science and Technology, 2025)
Air Traffic Control is the most critical component of Air Traffic Management, essential for ensuring passenger and aircraft safety as well as the commercial profitability of airlines. The problem studied remains quite broad and is based on decomposing the processing into several stages. This study aims to enhance traffic flow performance without altering the structure of the airspace. The paper explores two solutions for air traffic control: centralized and decentralized systems. The primary goal is to optimize air transport flows by selecting appropriate route networks and preventing collisions between aircraft. The analysis addresses the efficiency of these systems, considering the challenges posed by increasing air traffic volumes, and proposes innovative approaches for conflict resolution and system optimization. Additionally, the study considers potential benefits such as fuel savings and reductions in greenhouse gas emissions. The results demonstrate the potential of advanced automation and distributed systems to improve the efficiency and safety of air traffic management.